A phase I study of lenalidomide in patients with chronic myelomonocytic leukemia (CMML) – AGMT_CMML-1. Issue 5 (4th May 2018) - Burgstaller, Sonja; Stauder, Reinhard; Kuehr, Thomas; Lang, Alois; Machherndl-Spandl, Sigrid; Mayrbaeurl, Beate; Noesslinger, Thomas; Petzer, Andreas; Valent, Peter; Greil, Richard; Thaler, Josef
Abstract: According to former classification systems chronic myelomonocytic leukemia (CMML) is listed within myelodysplastic syndromes (MDS). Therefore data regarding treatment of CMML is largely derived from MDS trials. Two published studies suggest efficacy of lenalidomide in a proportion of patients with CMML, but the number of patients included was very low. We initiated this phase I trial with lenalidomide in patients with CMML. Primary objective of the current study was to determine the maximum tolerated dose (MTD). Secondary objectives were safety, tolerability and response. Twenty patients were enrolled and received lenalidomide using a classical 3 + 3 design. Lenalidomide 5 mg daily was confirmed as MTD. Best response achieved was partial remission in one patient and stable disease in nine patients. Lack of response with primary progressive disease was seen in three patients. Lenalidomide had a good toxicity profile in this study with thrombocytopenia being the main toxicity observed. Efficacy needs to be confirmed in further trials.